Sesquiterpene Glucosides from Nicotiana tabacum and Their Biological Activity - Yang, Guangyu-Yu; Zhao, Wei; Chen, Yong-Kuan; Chen, Zhang-Yu; Hu, Qiufen; Miao, Ming-Ming (Asian Journal of Chemistry, 2013)
A new sesquiterpene glucoside (1), together with two known sesquiterpene glucosides (2-3) were isolated from the leaves of Nicotiana tabacum. Their structures were elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compounds 1-3 were tested for their anti HIV-1 activities and cytotoxicity. The results showed that compounds 1-3 have weak cytotoxic abilities and anti HIV-1 bioctivities, respectively.